Optical probe of magnetic ordering structure and spin-entangled excitons in Mn-substituted NiPS3 - Lee, Je-Ho; Lee, Seungyeol; Choi, Youngsu; Gries, Lukas; Klingeler, Rüdiger; Raju, Kalaivanan; Ulaganathan, Rajesh Kumar; Sankar, Raman; Seong, Maeng-Je; Choi, Kwang-Yong (Advanced functional materials, 2024)
In van der Waals magnets, the interplay between magneto-excitonic coupling and optical phenomena opens avenues for directly probing magnetic ordering structures, manipulating excitonic properties through magnetic fields, and exploring quantum entanglement between electronic and magnetic states. Notably, NiPS3 stands out for its capacity to host spin-entangled excitons, where the excitonic states are intricately tied with the material's spin configuration. Herein, it is experimentally showcased that the spin-entangled excitons can be utilized for detecting the magnetic easy axis in Ni1-xMnxPS3 (x = 0-0.1). The end members of this series exhibit distinct magnetic ordering patterns and easy axes: zigzag ordering with magnetic moments aligned along the a-axis for NiPS3 versus Néel ordering with the out-of-plane easy axis for MnPS3. By combining angle-resolved exciton photoluminescence with magnetic susceptibility measurements, it is observed that the magnetic easy axis rotates away from the local spin chain direction with increasing Mn content. Moreover, through a comprehensive thermal and substitution study, it is demonstrated that the energy and lifetime of spin-entangled excitons are governed by two spin-flip processes and are drastically influenced by disparate electronic states. These findings not only provide optical means to map out magnetic ordering structures but also offer insights into decoherence processes in spin-exciton entangled states.
Veröffentlicht: 01 July 2024
Gesehen am 16.12.2024